Breakthroughs in Photonics 2013: Toward Feedback-Controlled Integrated Photonics - F. Morichetti (IEEE Photonics Journal, 2014)
We present an overview of the main achievements obtained in 2013 on the monitoring, stabilization, and feedback loop control of passive and active photonic integrated circuits. Key advances contributed to the evolution of photonic technologies from the current device level toward complex, adaptive, and reconfigurable integrated circuits.